Development of realistic physical breast phantoms matched to virtual breast phantoms based on human subject data - Kiarashi, Nooshin; Nolte, Adam C.; Sturgeon, Gregory M.; Segars, William P.; Ghate, Sujata V.; Nolte, Loren W.; Samei, Ehsan; Lo, Joseph Y. (Medical physics (Lancaster), 2015)
Purpose: Physical phantoms are essential for the development, optimization, and evaluation of x‐ray breast imaging systems. Recognizing the major effect of anatomy on image quality and clinical performance, such phantoms should ideally reflect the three‐dimensional structure of the human breast. Currently, there is no commercially available three‐dimensional physical breast phantom that is anthropomorphic. The authors present the development of a new suite of physical breast phantoms based on human data. Methods: The phantoms were designed to match the extended cardiac‐torso virtual breast phantoms that were based on dedicated breast computed tomography images of human subjects. The phantoms were fabricated by high‐resolution multimaterial additive manufacturing (3D printing) technology. The glandular equivalency of the photopolymer materials was measured relative to breast tissue‐equivalent plastic materials. Based on the current state‐of‐the‐art in the technology and available materials, two variations were fabricated. The first was a dual‐material phantom, the Doublet. Fibroglandular tissue and skin were represented by the most radiographically dense material available; adipose tissue was represented by the least radiographically dense material. The second variation, the Singlet, was fabricated with a single material to represent fibroglandular tissue and skin. It was subsequently filled with adipose‐equivalent materials including oil, beeswax, and permanent urethane‐based polymer. Simulated microcalcification clusters were further included in the phantoms via crushed eggshells. The phantoms were imaged and characterized visually and quantitatively. Results: The mammographic projections and tomosynthesis reconstructed images of the fabricated phantoms yielded realistic breast background. The mammograms of the phantoms demonstrated close correlation with simulated mammographic projection images of the corresponding virtual phantoms. Furthermore, power‐law descriptions of the phantom images were in general agreement with real human images. The Singlet approach offered more realistic contrast as compared to the Doublet approach, but at the expense of air bubbles and air pockets that formed during the filling process. Conclusions: The presented physical breast phantoms and their matching virtual breast phantoms offer realistic breast anatomy, patient variability, and ease of use, making them a potential candidate for performing both system quality control testing and virtual clinical trials.